Greece’s Trilateral Partnerships in the Balkans and the Black Sea Region and its Quest for National Security - Koukakis, Georgios (HAPSc Policy Briefs Series, 2024)
National security has always been of vital importance for Greece due to its small size and the variety of threats it encountered because of its strategic location. Thus, in an effort to enhance the majority of the components –military, economic, energy, maritime, cultural, domestic, etc.– of its national security, it has established several multilateral cooperative schemes in regional level. The purpose of the article is to briefly present the key events and main fields of cooperation of Greece’s trilateral partnerships that have been established in the Balkans and the Black Sea region –namely ‘Greece, Cyprus and Armenia’, ‘Greece, Cyprus and Serbia’, and ‘Greece, Bulgaria and Romania’– and assesses the contribution of these partnerships to the national security of Greece and the overall regional security.